INTERNET FINANCIAL REPORTING: MEDIA ANALISIS AKUNTABILITAS PERUSAHAAN FINANCIAL TECHNOLOGY - Novan Bastian Dwi Ardha (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2022)
This study aims to examine the implementation of accountability in the financial technology company in Indonesia. The degree of accountability is measured through financial reporting. This study employed qualitative research using content analysis method. The result of this study reveals that there are 30 out of 106 financial technology companies in Indonesia which apply internet financial reporting to the highest degree of accountability. This study contributes to the stakeholders of financial technology in order to take decision by comparing financial information disclosure between financial technology companies in Indonesia.